The Transformation of Marketing Communication through Social Media among Local MSMEs of the Baduy Luar Indigenous Community - Noor, Jabal; Maha, Srie Karina (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2025)
The digital era has transformed the dynamics of communication, economics, and cultural representation in various societies, including among Indonesia's indigenous communities. The Baduy Luar community, known for its strong adherence to traditional customs, is undergoing a gradual transformation through the use of digital platforms. This study explores how social media functions as a medium for marketing communication and cultural expression among local micro, small, and medium enterprises (MSMEs) within the Baduy Luar community. Using cultural communication and digital marketing perspectives, the study highlights how social media enables indigenous entrepreneurs to balance cultural authenticity with market visibility. Empirical observations indicate that social media has become an easily accessible and low-cost marketing tool that allows Baduy artisans to expand their markets while preserving traditional values. The integration of local identity, narrative authenticity,and digital marketing strategies forms a new model of indigenous marketing communication. The research findings indicate that the Baduy Luar community utilizes social media not as a symbol of modernization,but as a means of cultural expression and economic resilience. Digital media is utilized to expand market access while upholding ethical principles derived from ancestral traditions. This transformation presents a digital communication model rooted in local wisdom and aligned with ecological and moral responsibility. Theoretically,this research contributes to the development of value-oriented development communication studies. Practically, the results provide insights for policymakers and digital marketers in designing inclusive and culturally rooted communication strategies. The case of the Baduy Luar demonstrates that technological advancement, when guided by ancestral philosophies,can actually strengthen local identity.